Implementasi Python-PPTX dan Dom-to-Image dalam Pembangunan Sistem Otomatisasi Laporan Berbasis Web di PT. XYZ - Purbaningtyas, Mikha Kurnia Anggi; Susetyo, Yeremia Alfa (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
PT. XYZ is a leading retail company in Indonesia operating in a highly dynamic industry. Despite using PowerPoint (PPT) presentation reports as a key communication tool with its business partners, PT. XYZ's report creation process is still done manually. This leads to time wastage, the risk of errors, and disruptions to operational efficiency. The purpose of this research is to implement Python-pptx for the automation of report compilation and dom-to-image for the integration of visual data. The goal is to overcome the main challenges faced by PT. XYZ. The research methodology includes problem identification, literature review, system requirements analysis, system design, application development, and system testing. The results of this research include the successful implementation of Python-pptx and dom-to-image in building a web-based automated reporting system at PT. XYZ. System testing demonstrates the success of this technology, ensuring user satisfaction, and preparing the system for more efficient use.